La valorizzazione economica delle tipicità rurali tra localismo e globalizzazione - Cristiano, Ciappei (Firenze University Press, 2006)
For over twenty years now, the agri-foodstuffs sector has been marked by an ongoing revaluation of the typical product. Such products encompass an increasingly intangible value connected, not only with their intrinsic qualities, but also with what is evoked by the production methods and the context from which they originate. The typical product is identified by a decided stability in the features, deriving from the concentration of a major historic tradition in geographically small territories by a relatively restricted human group. As a result, in general, the local identity tends to predominate over the image of the firm. This accentuates the most significant strategic phenomenon: the collaboration between direct competitors implemented by the producers.